The Trickster Figure in American Literature - Morgan, Winifred. author. aut Link
VII, 256 p.
Keywords: This book analyzes and offers fresh insights into the trickster tradition including African American, American Indian, Euro-American, Asian American, and Latino/a stories, Morgan examines the oral roots of each racial/ethnic group to reveal how each group's history, frustrations, and aspirations have molded the tradition in contemporary literature.